Polyploid cell dynamics and death before and after PEG-treatment of a NIH/3T3 derived culture: vinblastine effects on the regulation of cell subpopulations heterogeneity - Alessandra Spano; Luigi Sciola (Cell Division, 2023)
Abstract Background Neoplastic subpopulations can include polyploid cells that can be involved in tumor evolution and recurrence. Their origin can be traced back to the tumor microenvironment or chemotherapeutic treatment, which can alter cell division or favor cell fusion, generating multinucleated cells. Their progeny, frequently genetically unstable, can result in new aggressive and more resistant to chemotherapy subpopulations. In our work, we used NIHs cells, previously derived from the NIH/3T3 line after serum deprivation, that induced a polyploidization increase with the appearance of cells with DNA content ranging from 4 to 24c. This study aimed to analyze the cellular dynamics of NIHs culture subpopulations before and after treatment with the fusogenic agent polyethylene glycol (PEG), which allowed us to obtain new giant polyploid cells. Successively, PEG-untreated and PEG-treated cultures were incubated with the antimicrotubular poison vinblastine. The dynamics of appearance, decrease and loss of cell subpopulations were evaluated by correlating cell DNA content to mono-multinuclearity resulting from cell fusion and division process alteration and to the peculiarities of cell death events. Results DNA microfluorimetry and morphological techniques (phase contrast, fluorescence and TEM microscopies) indicated that PEG treatment induced a 4–24c cell increase and the appearance of new giant elements (64–140c DNA content). Ultrastructural analysis and autophagosomal–lysosomal compartment fluorochromization, which allowed us to correlate cytoplasmic changes to death events, indicated that cell depletion occurred through distinct mechanisms: apoptotic death involved 2c, 4c and 8c cells, while autophagic-like death involved intermediate 12–24c cells, showing nuclear (lobulation/micronucleation) and autophagic cytoplasm alterations. Death, spontaneously occurring, especially in intermediate-sized cells, was increased after vinblastine treatment. No evident cell loss by death events was detected in the 64–140c range. Conclusions PEG-treated NIHs cultures can represent a model of heterogeneous subpopulations originating from cell fusion and division process anomalies. Altogether, our results suggest that the different cell dynamics of NIHs subpopulations can affect the variability of responses to stimuli able to induce cell degeneration and death. Apoptptic, autophagic or hybrid forms of cell death can also depend on the DNA content and ability to progress through the cell cycle, which may influence the persistence and fate of polyploid cell descendants, also concerning chemotherapeutic agent action.